Seasonal occurrence of spotted wing drosophila in various small fruits and berries in Pennsylvania and Maryland. (29th April 2016) - Joshi, N. K.; Butler, B.; Demchak, K.; Biddinger, D.
Abstract: Spotted wing drosophila (SWD) ( Drosophila suzukii ), a major invasive pest of small fruit crops, was first found in Pennsylvania and Maryland during the 2011 crop season, and since then, it has been established throughout the fruit growing regions of both states. A season‐long field study was conducted to find out the seasonal occurrence of SWD in several fruit crops (e.g. blueberry, tart and sweet cherry, floricane‐fruiting summer red raspberry, blackberry, primocane‐fruiting fall raspberries and table grapes) in Pennsylvania and Maryland in 2014. This is the first study determining seasonal occurrence of SWD using a standard commercial lure (Pherocon ® SWD Dual‐Lure ™ )‐baited traps in this region. In both states, SWD adults were not captured prior to the month of July, and populations of SWD were found to build up in fruit crops only from mid‐July onwards. This indicates early season fruit crops or varieties are not at risk from SWD fruit injury in these two states. Such early fruit crops, for instance strawberry, sweet and tart cherry, are generally harvested before SWD populations build up in this region. In this context, implications of SWD population in various small fruit crops grown in this region and the utility of SWD Dual‐Lure ™ in season‐long monitoring of SWD population are discussed.